Effect of umbilical cord mesenchymal stem cells on hypoxia-inducible factor-1 alpha (HIF-1α) production in arteriovenous fistula (AVF) animal model: A preliminary study - Habibie, Yopie A.; Emril, Dessy R.; Azharuddin, Azharuddin; Syahrizal, Dedy (Narra Sains Indonesia, 2023)
Hypoxia-inducible factor-1 alpha (HIF-1α) is a transcription factor that plays a crucial role in cellular responses to hypoxia, such as in the development of intimal hyperplasia, a common complication in arteriovenous fistula (AVF) creation. While the application of umbilical cord mesenchymal stem cells (UC-MSCs) has shown promise in various regenerative medicine applications, including tissue repair and angiogenesis, the effect of UC-MSCs on HIF-1α level in the AVF has not been tested. Therefore, the aim of this study was to evaluate the effect of UC-MSCs administration on HIF-1α levels in the AVF animal model. An experimental study was conducted on 28 local male rabbits (Lepus domestica) using a post-test-only design. The rabbits were divided randomly into four groups: normal rabbit group (negative control), placebo-treated AVF rabbit group (positive control), AVF rabbits treated with in-situ UC-MSCs injection (one dose, 106 UC-MSCs/kg body weight), and AVF rabbits treated with intravenous UC-MSCs (one dose, 106 UC-MSCs/kg body weight (BW). HIF-1α level was measured using ELISA method after 28 days post- treatment. All data were analyzed using the one-way analysis of variance (ANOVA) and continued with the Duncan’s post-hoc test. The data indicated that the levels of HIF-1α were different among all four groups (p<0.001). The post-hoc analysis revealed that the HIF-1α levels in both UC-MSC treated groups were significantly lower compared to untreated AVF rabbits(p<0.05). This study suggests that UC-MSCs could be a promising therapy to prevent and reduce intimal hyperplasia in AVF.